Fine‐scale climate variability in a complex terrain basin using a high‐resolution weather station network in southeastern Brazil. (1st October 2018) - Martin, Thomas C.; da Rocha, Humberto R.; Joly, Carlos A.; Freitas, Helber C.; Wanderley, Raianny L.; da Silva, Jonathan M.
Abstract : Montane climates are shaped by high spatial variability that depends on net radiation and synoptic weather, and much on elevation and topographic features of terrain. We measured near‐ground meteorological variables using a weather station network during 14 months, in a valley‐shaped basin in southeast Brazil, to address the spatiotemporal climate variability at the meso‐ γ atmospheric scale. The terrestrial climatic gradients were evident in the cross‐valley direction of the basin, where the valley tended to warm/wet up at day and cool/dry down at night relatively from the slopes. The temperature at noon showed high variability and decreased at a mean gradients of about −0.7 °C (100 m) −1 . The nocturnal air temperature increased with height up to a maximum at about 200 m (the thermal belt), and showed seasonal rates higher/less in dry/wet season of +1.1/+0.2 °C (100 m) −1 over the full altitude. The vapour pressure decreased from the valley bottom upwards, in general below −0.5 hPa (100 m) −1, whereas the wind speed increased at a rate of 0.9 m s −1 (100 m) −1 . We noted significant differential warming along the valley and mountain sides. The middle valley was circumstantially colder at night and warmer at daytime, relatively to the upper catchment, under mean magnitudes below 1.0 °C. The west slope at upper catchment was slightly warmer at night, and colder in the afternoon, at magnitudes below 0.5 °C, highlighting the control of hills' aspect at daytime, and the sheltering to flow aloft in east side. The cross‐valley gradients appeared to be well associated with local circulation, where downslope wind and positive temperature gradients, as well as upslope wind and negative temperature gradients strictly coexisted during the morning. The terrestrial gradients and the thermal circulation were in general dampened by cloudiness and mechanical mixing. Abstract : This paper presents the spatiotemporal variability of near‐surface temperature, specific humidity and wind across the landscape of a mesoscale basin in southeast Brazil. We show the daily and seasonal variation of climatic gradient across the catchment and the characteristics of the thermally driven wind circulation and highlighted the influence of the topography and synoptic weather conditions.